Chemical characterization of tobacco-free "modern" oral nicotine pouches and their position on the toxicant and risk continuums. (3rd September 2022) - Azzopardi, David; Liu, Chuan; Murphy, James
Abstract: As compared with cigarette smoking, use of Swedish snus is associated with significantly fewer health risks. Nicotine pouches (NPs), a new form of oral nicotine product, are smokeless and tobacco-free, comprising a nicotine-containing cellulose matrix inside a fiber pouch. NPs are similar in appearance/use to snus, but without tobacco, have the potential to further reduce tobacco-related harm. This study aimed to evaluate toxicant levels of NPs to estimate their position on the tobacco/nicotine product continuums of toxicant delivery and risk. NPs, snus and nicotine replacement therapy products (NRTs) were analyzed for 24–26 compounds applicable to oral tobacco, and their levels were compared. Twenty of these compounds were further used to compare the toxicant profile of NPs, as well as estimated daily toxicant exposure from NP use, with that of tobacco/nicotine products spanning the risk continuum. Of the compounds measured, 22 (NPs), 22 (lozenge NRT), 20 (gum NRT), and 11 (snus) were not quantifiable. Compared with snus, NPs had lower levels of 10 HPHCs and comparable/undetectable levels of a further 13. Across the product categories, NPs and NRTs had the lowest toxicant profiles and estimations of relative toxicant exposure. Based on the present chemical analysis and estimated exposure, use of NPs appears likely to expose users to lower levels of toxic compounds than Swedish snus, which is recognized to offer reduced levels of harm than associated with tobacco smoking. We conclude that NPs should be placed close to NRTs on the tobacco/nicotine product toxicant delivery continuum, although further studies will be needed to confirm this.